OP0098 The detection of a potentially pathogenic subset of HLA-B27 conformers at the cell surface in a rat model of SPA. (23rd January 2014) - Mchugh, K.; Shaw, J.; Kollnberger, S.; Utriainen, L.; Firmin, D.; Milling, S.; Renner, C.; Bowness, P.
Abstract : Background: The MHC class I antigen HLA-B27 (B27) is strongly associated with development of SpA, yet the mechanism by which B27 confers this susceptibility is unclear. B27 exists at the cell surface as fully conformed heterotrimers (B27HT) associated with peptide and b2 m, but also as peptide-free heavy chain monomers (B27HC) and heavy chain homodimers (B272 ), which we have shown to interact with innate immune receptors in a distinct manner to B27HT. A pathogenic role for these receptor interactions has been proposed. Objectives: This study aimed to analyse the expression of these potentially pathogenic aberrant forms of B27 in splenocytes isolated from B27 TG rats through the use of a novel B27-specific monoclonal antibody, HD6. Methods: Splenic mononuclear cells from age-matched adult (6-9 months) B27 transgenic (TG), B7 TG, and non-transgenic (NT) rats were compared for staining with the monoclonal antibodies HD6, HC-10, HLA-ABC-m1 and an IgG1 isotype control. Staining was also compared in splenocytes isolated from young clinically healthy B27 TG rats (5-10 weeks) with those from the adult B27 TG rats. For further characterisation of the HD6 epitope, splenocytes were cultured with HLA-B27-binding or control peptides prior to FACS analysis. Results: HD6 staining was consistently seen in the lymphocyte and macrophage/DC populations for adult B27 TG samples. Notably, however, no HD6 staining above background was observed in the granulocyte gate, which was also the case for HC-10. Within the lymphocyte, gate, comparable staining was seen for the CD4+ and CD8+ cell populations. HD6 staining was B27-specific, as B7 TG rat splenocytes consistently failed to stain with HD6, despite similar expression of human MHC class I molecules. Expression of folded HLA-B27 was increased in the older B27 TG rats compared to the younger B27 TG rats, consistent with previous reports, as was expression of free heavy chains. However, very little detectable HD6 staining was observed in cell subsets from the younger rats. HD6 staining was inhibited by incubation of splenocytes with B27-binding peptides. Conclusions: These data demonstrate cell surface expression of HD6-reactive molecules on a number of cell subsets from HLA-B27 transgenic rats. Moreover, HD6 surface staining is strongly correlated both with the degree of B27 expression and with age. HD6 binding can be inhibited by incubation with B27-binding peptides, suggesting that it detects a population of peptide-free aberrant cell surface B27 conformers. Our data is consistent with the hypothesis that altered immune interactions, as a consequence of the presence of aberrant forms of HLA-B27 at the cell surface, contribute to SpA pathogenesis. Disclosure of Interest: None Declared